The Principal's Strategy in Improving Student Achievement at Darunnajah Islamic Boarding School Jakarta - Nashiruddin Cholid; Helmi Yusuf (Edukasiana: Journal of Islamic Education, 2023)
Abstract This research aims to determine and describe the strategies implemented by school principals in improving student learning achievement at the Darunnajah Islamic Boarding School, Jakarta. The research method used is qualitative with a case study approach. Data collection was carried out through in-depth interviews, observation and documentation studies. The research results show that school principals play an important role in improving student learning achievement by implementing several strategies, including: (1) Creating systematic and planned educational programs; (2) Improving the quality of educators and education personnel through training and professional development; (3) Encourage active involvement of parents in the teaching and learning process; and (4) Using technology in the learning process to increase teaching effectiveness. Apart from that, collaboration between aspects of the curriculum, character building and extracurricular activities is also a supporting factor in improving student learning achievement. It is hoped that this research can become a reference for other educational institutions in formulating strategies to improve student learning achievement.